PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS, UKURAN PERUSAHAAN, DAN KOMISARIS INDEPENDEN TERHADAP AGRESIVITAS PAJAK (Studi pada Perusahaan Pertambangan dan Pertanian yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2016) - Siti Aisyah Putri Rasyidin; Nasrizal Nasrizal; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the effect of liquidity, leverage, firm size, and independent commissioner against tax aggressiveness in mining and agriculture companies listed in the Indonesia Stock Exchange. The research data is secondary data in the form of the annual reports of companies. While the population in this study are all mining and agriculture companies listed in the Indonesia Stock Exchange during 2013-2016. Selection of the sample using purposive sampling method in which the population of 64 selected according to criteria of a sample of 13 companies selected. The data analysis used is multiple regression. The results of this study show that liquidity no effect on the tax aggressiveness with significant value of 0,625, leverage no effect on the tax aggressiveness with significant value of 0,899, profitability has negative effect on the tax aggressiveness with significant value of 0,02, firm size no effect on the tax aggressiveness with significant value of 0,754, and independent commissioner has negative effect on the tax aggressiveness with significant value of 0,032. The coefficient of determination in this study 0,200 shows that 20% of the variations that occur in the tax aggressiveness is affected by liquidity, leverage, profitability, firm size, as well as independent commissioner and the remaining 80% is influenced by other variables not included in this research.Keyword : Liquidity, Leverage, Profitability, Firm Size, Independent Commissioner, and Tax Aggressiveness.